The Central Idea of the Text on the Benefits of Spices: Ide Sentral Naskah Khasiat Rempah-rempahan - Rahmatillah; Hermansyah; Ruhamah (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
This Text on the Benefits of Spices is an Arabic-Malay text that discusses the properties of spices as medicine. This manuscript is from the Pedir Museum collection with inventory number MS.PM.0432/2019 which is included in a collection of texts totaling 94 pages. This research was carried out because there are still many manuscripts that have not been studied thoroughly and the condition of the manuscripts needs serious treatment, as a result the information in the manuscripts cannot be understood perfectly. So the aim of this research is to produce edits to the text so that it can be read correctly and highlight the central ideas contained in the text on the properties of spices as useful information for society. Because this manuscript is a single manuscript, the researcher used a single manuscript research method with a standard edition. Apart from that, researchers also used the theory of the use of herbs in the world of health to study the text. The central idea contained in this text is the spices used for treatment, some of these spices are black cumin, hinggu, kerosene, ginger, shallots, garlic, ma'jun, coriander, nutmeg, wheat rice, cloves, vinegar sour, and moist. The results of this research show that, first: edit the text to a standard edition, and second: clearly understand the contents of the text on the properties of spices which discusses how to use spices for treatment.